Design and Construction of 2.4 Ghz Omnidirectional Antenna as Wireless LAN Transmitter (Case Study at Bukit Indah Campus, Malikussaleh University) - Rizal Tjut Adek; Rahmat Rinaldi; Ilham Sahputra; Mukhlis (Universitas Medan Area, 2023)
Communication with a wireless system is one of the mainstay communications so that communication integration is achieved. For this reason, Malikussaleh University provides a wifi network on each campus, one of which is the Bukit Indah campus. So that the achievement of wifi access points on mobile devices needs to be improved so that it is achieved properly. Therefore it is necessary to optimize the placement of access points on the Malikussaleh University wifi network. Modeling an omnidirectional antenna that has a range of 360 ° is one solution. The method applied is to design and build an omnidirectional antenna on the Bukit Indah Campus of Malikussaleh University. Based on simulations on Mobile Radio, the largest network pathloss is 116.2 dB and the smallest is 102.0 dB. The results of omidirectional antenna testing conducted 5 times obtained the largest download speed worth 3.18 Mbps with 314ms ping at a distance of 30 meters and the smallest download speed worth 0.55Mbps with 195ms ping at a distance of 150 meters. The farther the distance of the antenna the lower the ping and packet loss, from the test results obtained an average ping of 267.8ms and the largest packet loss percentage of 0.4%. The ideal distance for this antenna is 30 to 110 meters and can even get a longer distance provided there are no obstacles. With this distance it is ideal for an assembled antenna with makeshift materials that we often encounter in everyday life.